Promoting Students’ Reviewing Skills in Foreign Language Writing through Genre-Based Activities in Linguistic Classes - Tam Nguyen (Universitas Muhammadiyah Yogyakarta, 2022)
Recently, genre studies contribute not only to linguistic areas but also to the areas of language education. In language teaching and learning, developing learners’ awareness of various genres, especially those prevail in their future job contexts, is essential in the sense that learners could be better prepared to successfully produce texts of the same genres when required. In this study, genre-based activities (GBAs) were introduced to 40 third-year EFL students in two linguistic classes. The data collection was conducted via class interaction, assignment analysis and informal talks. The data analysis revealed that, despite some limitations in the intervention, GBAs had such positive effects on students’ development of reviewing skills in English writing as: students could link their text evaluation and revision to the contextual features, they tried to read extensively about the features of different genres, and accordingly, they could enhance their genre awareness, resulting in their better evaluation and revision of texts. However, it was found that unfamiliar genres might hinder the effects of GBAs. Texts elicited from students and multimodal texts were more appropriate inputs for novice genre analysts.